A review on biological effects of Lamium album (white dead nettle) and its components - Tahere Pourmirzaee Sheikhali Kelayeh; Mahmood Abedinzade; Ahmad Ghorbani (Shahrekord University of Medical Sciences, 2019)
Lamium album, commonly known as white dead nettle, is a plant in the family of Lamiaceae. This plant is distributed all over Asia, Europe, and Africa. In the traditional medicine of Asia, it has been used for the treatment of a number of diseases such as trauma, fracture, paralysis, leucorrhoea, hypertension women's pain, uterine hemorrhage, menorrhagia, vaginal and cervical inflammation. In recent years, L. album has been the subject of intensive experimental studies to evaluate its traditional use to reveal new biological properties. A wide range of pharmacological effects, including antimicrobial, anti-inflammatory, anticancer, and antidiabetic properties have been reported by these studies. This review presents an up-to-date overview of the current literature on the pharmacological and physiological effects of L. album. Also, phytochemical constituents responsible for the biological properties of L. album are presented and discussed.